1996
DOI: 10.1093/humupd/2.6.519
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial pelvic inflammatory disease

Abstract: Pelvic inflammatory disease (PID) is the most important complication present in the female lower genital tract, causing major medical, social and economic problems. Although PID can be caused by multiple microorganisms, it results most frequently from the ascent of sexually transmitted Chlamydia.trachomatis or Neisseria gonorrhoeae infections from the cervix to the upper genital tract. The importance of cervical chlamydial infection in the pathogenesis of PID is well recognized. Recent data from many developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 101 publications
0
35
0
Order By: Relevance
“…C. trachomatis is an obligate intracellular Gram-negative bacterium, which, like all chlamydial species, has a tendency to cause chronic persistent infections. In women, chronic C. trachomatis infections have been connected to pelvic inflammatory disease, ectopic pregnancies, and infertility (13)(14)(15). Furthermore, our earlier seroepidemiologic studies have suggested that chronic C. trachomatis infections increase the risk of cervical cancer (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…C. trachomatis is an obligate intracellular Gram-negative bacterium, which, like all chlamydial species, has a tendency to cause chronic persistent infections. In women, chronic C. trachomatis infections have been connected to pelvic inflammatory disease, ectopic pregnancies, and infertility (13)(14)(15). Furthermore, our earlier seroepidemiologic studies have suggested that chronic C. trachomatis infections increase the risk of cervical cancer (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Although up to 94% of women with urogenital chlamydial infections do not manifest obvious symptoms (20,28), the consequences of such untreated infections, including pelvic inflammatory disease, ectopic pregnancy, and infertility (27), generate a global financial burden of billions of dollars annually. Because most infected individuals are either asymptomatic or have mild, nonspecific symptoms, C. trachomatis infection poses a problem for health control programs.…”
mentioning
confidence: 99%
“…From here, the bacteria ascend and establish infection in columnar cells of human fallopian tubes or oviducts in mice. Left untreated, human infection can lead to pelvic inflammatory disease, fallopian tube injury, and infertility (22). Oviduct injury, characterized by hydrosalpinx, and infertility are also seen in murine infections (33).…”
mentioning
confidence: 99%